2021
DOI: 10.1097/cm9.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

The role of FGF21 in the pathogenesis of cardiovascular disease

Abstract: The morbidity and mortality of cardiovascular diseases (CVDs) are increasing worldwide and seriously threaten human life and health. Fibroblast growth factor 21 (FGF21), a metabolic regulator, regulates glucose and lipid metabolism and may exert beneficial effects on the cardiovascular system. In recent years, FGF21 has been found to act directly on the cardiovascular system and may be used as an early biomarker of CVDs. The present review highlights the recent progress in understanding the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 147 publications
(347 reference statements)
0
14
0
Order By: Relevance
“…In the cardiovascular system, FGF21 exerts a protective function on endothelial cells by resisting oxidative stress, inhibiting aberrant vascular remodeling, and antagonizing angiotensin II [ 47 , 48 , 49 , 50 ]. Studies have demonstrated that FGF21 can also significantly reduce fasting blood glucose level and improve glucose clearance without hypoglycemia [ 51 , 52 , 53 , 54 ]. Significant FGF21 production in the liver and enhanced circulating FGF21 may, therefore, contribute to the beneficial effects of PEM.…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiovascular system, FGF21 exerts a protective function on endothelial cells by resisting oxidative stress, inhibiting aberrant vascular remodeling, and antagonizing angiotensin II [ 47 , 48 , 49 , 50 ]. Studies have demonstrated that FGF21 can also significantly reduce fasting blood glucose level and improve glucose clearance without hypoglycemia [ 51 , 52 , 53 , 54 ]. Significant FGF21 production in the liver and enhanced circulating FGF21 may, therefore, contribute to the beneficial effects of PEM.…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 can induce cardiac protection by preventing cardiac lipotoxicity, oxidative stress, and inflammation by directly binding to the FGFR of the heart [222]. However, in another multiethnic clinical study, FGF21 was not a CVD biomarker in atherosclerosis patients without known CVD [44].…”
Section: Fgf21: As a Biomarker For Metabolic And Cardiovascular Diseasesmentioning
confidence: 95%
“…In addition, mechanistic studies revealed that FGF21 can act directly on the cardiovascular system and may be used as an early biomarker of CVD. FGF21 can induce cardiac protection by preventing cardiac lipotoxicity, oxidative stress, and inflammation by directly binding to the FGFR of the heart 222 . However, in another multiethnic clinical study, FGF21 was not a CVD biomarker in atherosclerosis patients without known CVD 44 .…”
Section: Summary Of Fgf21 In Cvmdmentioning
confidence: 99%
“…When FGF binds to its receptors, it mediates intracellular signaling through four pathways: RAS/RAF/mitogen-activation protein kinase (MAPK) signaling pathway, phosphatidylinositol 3-kinase (PI3K)/serine-threonine protein kinase AKT signaling pathway, signal transducer and activator of transcription (STAT) signaling pathway, and phosphoinositide phospholipase C (PLC) γ signaling pathway ( 78 , 79 ). FGF21 contains 209 and 210 amino acid residues in humans and rodents, respectively; it consists 13 N-terminal residues and 40 C-terminal residues and the gene encoding FGF21 is located on chromosome 19 ( 80 ). The activation of the FGFR1 receptor by FGF21 requires the involvement of the cofactor β-klotho ( 81 ).…”
Section: Myokines and Dnmentioning
confidence: 99%